STUDY ON THE EFFECT OF BIOAUGMENTATION ON THE REDUCTION OF AMMONIA IN THE SEDIMENT OF SEMI INTENSIVE TAMBAK - Sarjito .; Adi Santoso; Ali Djunaedi (JOURNAL OF COASTAL DEVELOPMENT, 2000)
The aboraratory scale experiment with split plot randomized design was perfomed to find out the effect bioaugmention on ammonia reduction in the sediment of semi intensive tambak. The msin treatment was bioaugmentaion with probiotic epicin concentration of 0; 0.5 ; 1.0 and 1.5 ppm; as sub-treatment was the salinity (20; 25 and 30 ppt), and as a group was day (0; 2; 4 and 6). The result indicated that bioaugmentation was able to reduce ammonia concentration in the sediment of semi intensive tambak. The treatments, especially dose and days had a significant affect on the reduction ammonia in the sediment (p<0.01) with exception to salinity (p>0.05). the capability of epicin as a bioaugmentation started on the day of 2. The most effective epicin dose to reduce ammonia in the sedimentof semi intensive tambak for culture of Tiger shrimp (Penaeus. Monodon F.) was 1.5 ppm.